Peningkatan Hasil Belajar Peserta Didik Kelas V melalui Pendekatan Tarl pada Mata Pelajaran Bahasa Indonesia di UPT SD Negeri 060843 Medan Barat - Hanan Alfaraha; Mimi Rosadi; Sujarwo Sujarwo; Emce Ida Hutabarat; Khairu Fadli (Departement of Mathematics Education, 2024)
The Merdeka Curriculum is a reference for developing abilities and teachers are freed to create learning tools. The Independent Curriculum creates flexible learning for students and educators. Low learning outcomes have an impact on student motivation and learning outcomes due to many factors such as lack of parental support and understanding of the importance of education. The method used in this research is classroom action research (PTK). PTK is carried out using the Teaching at The Right Level (TaRL) approach and the Problem Based Learning (PBL) model. This research aims to see improvements in student learning outcomes through the TaRL approach in Indonesian language subjects at UPT SD Negeri 060843 West Medan. This research was carried out using II Cycles, each stage of which is in accordance with the model from Suharsimi Arikunto (2021) which is formed from design, implementation, observation and feedback. Based on the research that has been conducted, it can be concluded that the application of the TaRL approach to improve student learning outcomes is going well and successfully. It can be seen from the results of observations of teacher activity in cycle I which reached 80% then increased in cycle II to 90%. Likewise, the results of student observations in cycle I reached 80% and increased in cycle II to 90%. The learning outcomes of class V students have increased significantly. It can be proven based on the percentage of complete learning outcomes of students who obtained 70% in the pre-cycle, then by carrying out classroom actions the results increased to 80% in cycle I and 90% in cycle II.